A Selective Role for MRF4 in Innervated Adult Skeletal Muscle: Na(V) 1.4 Na(+) Channel Expression Is Reduced in MRF4-Null Mice - Thompson, Amy L. (Gene Expr, 2018)
The factors that regulate transcription and spatial expression of the adult skeletal muscle Na(+) channel, Na(V) 1.4, are poorly understood. Here we tested the role of the transcription factor MRF4, one of four basic helix–loop–helix (bHLH) factors expressed in skeletal muscle, in regulation of the Na(V) 1.4 Na(+) channel. Overexpression of MRF4 in C2C12 muscle cells dramatically elevated Na(V) 1.4 reporter gene expression, indicating that MRF4 is more efficacious than the other bHLH factors expressed at high levels endogenously in these cells. In vivo, MRF4 protein was found both in extrajunctional and subsynaptic muscle nuclei. To test the importance of MRF4 in Na(V) 1.4 gene regulation in vivo, we examined Na(+) channel expression in MRF4-null mice using several techniques, including Western blotting, immunocytochemistry, and electrophysiological recording. By all methods, we found that expression of the Na(V) 1.4 Na(+) channel was substantially reduced in MRF4-null mice, both in the surface membrane and at neuromuscular junctions. In contrast, expression of the acetylcholine receptor, and in particular its α subunit, was unchanged, indicating that MRF4 regulation of Na(+) channel expression was selective. Expression of the bHLH factors myf-5, MyoD, and myogenin was increased in MRF4-null mice, but these factors were not able to fully maintain Na(V) 1.4 Na(+) channel expression either in the extrajunctional membrane or at the synapse. Thus, MRF4 appears to play a novel and selective role in adult muscle.